An e-culture – e-museums environment for common citizens and disabled individuals. (20th May 2009) - Drigas, Athanasios; Koukianakis, Leyteris; Glentzes, John
The integration of modern information and communication technologies (ICTs) within the cultural domain creates what is commonly known as e-culture. The need to create an e-culture environment arose from the undeniable fact that the cultural heritage of a nation defines it and, therefore, should be disseminated to all, regardless of their location and their disability. This article discusses an e-culture portal, which presents to any interested users, information regarding a significant number of Greek and Cypriot museums and galleries as well as their exhibits. The e-culture environment offers user-friendly navigation techniques and contemporary multimedia tools and services for the better presentation and visualisation of the e-material to the users-visitors, paying particular attention to both common citizens and to disabled individuals, in order to offer them equal access to cultural heritage information. This environment is an inter-disciplinary application, combining the ICTs, cultural and e-inclusion domains (electronic support for disabled people).